Pengaruh Tipe Keterlibatan Konsumen Terhadap Kepercayaan Merek Dan Dampaknya Pada Keputusan Pembelian Sepeda Motor Di Kota Lamongan - Masruroh; Kusumawan, Ardie (CV. Multi Kreasi Media, 2024)
The purpose of this research is examining the influence of type of consumer involvement on the brand trust to the purchase decision for the motorcycle in Lamongan. The instrument of this article is Path Analysis. This research design applies confirmatory study that uses survey approach. The primary data is obtained non probability with purposive sampling methode. The respondence are consumer who is purchase in the motorcycle dealer in Lamongan.The result of this research shows that the type of consumer involvement positively influence to the brand trust to the purchase decision,there is positively influence for brand trust to purchase intention,the variable of situational involvement have dominant influence to the brand trust and purchase intention. There are direct influence to the type of involvement to purchase intention while the brand trust as mediator.